Urochloa humidicola breeding: Selection based on hybrid performance in multi-environmental trial on Bh22 population - Hernández, Luis Miguel; Camelo, Rodrigo; Jauregui, Rosa (CGIAR Initiative on Accelerated Breeding, 2023)
In 2022, a new cohort of U. humidicola hybrids was obtained and named Bh22. This cohort was composed of 5,024 hybrids and corresponded to the 3rd cycle of recurrent selection. Out of 5,024 individuals tested, 1,887 were identified as apomicts through the molecular marker p779/p780 (Worthington, 2016). In 2023, with the objective to select i) a subset of genotypes based on their performance and ii) mothers based on hybrid performance, a multi-environment trial was implemented. This report summarizes activities conducted to implement field experiments in three locations: Llanos, Quilichao, and Palmira.